Medical consequences of working at the computer on human health. - Adrian Bartoszek; Wojciech Korga; Kamil Szalast; Andrzej Sagan (Kazimierz Wielki University, 2018)
Introduction In the modern world, the computer has become a device of universal use, both at work, at home and in leisure time. Health effects resulting from working at the computer are associated with taking a wrong position while using the computer and the influence of the electromagnetic field emitted by LCD monitors. The most common health problems among computer users include eye, musculoskeletal, nervous and cardiovascular disorders. Aim Presenting the medical consequences of working at the computer and using the LCD monitor for human health, including the eyes, musculoskeletal system, nervous system and circulatory system. Conclusions Most people working at a computer sooner or later will experience various health problems. Some of these problems, such as visual disturbances, chronic venous insufficiency, neck and spine pains, will be intensified due to work with a computer. It is important to take measures to prevent the deterioration of health, by observing the principles of ergonomics while working, performing eye exercises, frequently changing the position of the body, taking breaks while working at the computer and spending free time in an active way.